Anti-malaria prescription in pregnancy among general practitioners in Enugu state, south east Nigeria - Ugwu, Emmanuel Onyebuchi (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: The national policy on malaria control recommends use of intermittent preventive treatment with sulfadoxine/pyrimethamine (IPT-SP) for chemoprophylaxis against malaria in pregnancy; and use of quinine and arthemisinin-based combination therapy (ACT) for acute treatment of malaria in the first, and second/third trimesters, respectively. In Nigeria, a large proportion of pregnant women are seen by the general practitioners (GPs). OBJECTIVE: To determine the pattern of anti-malaria prescription in pregnancy among GPs in Enugu state, and access the level of conformity with the national policy on malaria control. MATERIALS AND METHODS: Questionnaires were administered to a cross-section of 147 GPs that attended the 2010 Enugu state branch of the Nigeria Medical Association Scientific Conference/Annual General Meeting/Election. RESULTS: The mean age of the GPs was 37 ± 3.6 (range 27-70) years. Quinine was the commonly (45.6% (n = 67)) prescribed anti-malaria drug in the first trimester while in the second/third trimester ACT was commonly (48.3% (n = 71)) prescribed. Seventy-six (51.7%) practitioners prescribed IPT-SP for chemoprophylaxis against malaria while the rest (48.3%) prescribed other drugs. GPs who obtained MBBS qualification less than or equal to 5 years prior to the survey were more likely to comply with the national policy on malaria control in their prescriptions (P < 0.05). CONCLUSION: The pattern of anti-malaria prescription among GPs in Enugu state is varied, and conformed poorly to the evidence-based national policy on malaria control. There is need for continuing professional development to keep the GPs abreast with current trends in malaria treatment during pregnancy.